Little mind benders - Mohtarrudin, Norhafizah; Kassim, Fauziah; Ahmad Sharifuddin, Fatimah (Universiti Putra Malaysia Press, 2016)
Toxoplasma gondii is a unique yet dangerous protozoan parasite. It sneaks into the brain and alters the host’s behaviour and health. Imagine how these tiny little creatures invading the brain and becoming the inner companions, hanging out and wandering freely in the host’s brain. These little creatures possess mind altering ability that can reform the host’s central nervous system.